Corporate Social Responsibility Reporting and Its Influence on Firm Value (gjstudies, 2014)
This study investigates the nuanced relationship between Corporate Social Responsibility (CSR) reporting and firm value, moving beyond traditional linear models topropose a novel, threshold-based framework. While extant literature predominantlyexamines CSR as a monolithic construct with uniform financial implications, this research posits that the value relevance of CSR reporting is contingent upon a firm’sstrategic positioning and the materiality of its disclosed activities. We introduce theconcept of ’Strategic CSR Congruence’—the alignment between a firm’s core businessoperations and its reported CSR initiatives—as a critical moderating variable. Utilizing a hand-collected dataset of 450 publicly traded firms from 1998 to 2004, weemploy a multi-method approach combining content analysis of CSR reports, financial statement data, and market valuation metrics. Our methodology innovativelyapplies latent class analysis to categorize firms based on their CSR reporting profiles,rather than relying on aggregate scores. The results reveal a non-linear, inverted Ushaped relationship between the extensiveness of CSR reporting and Tobin’s Q. Firmsdemonstrating high Strategic CSR Congruence experience significant positive marketreactions, whereas firms with extensive but incongruent reporting exhibit a valuationdiscount. Furthermore, we identify a reporting threshold; beyond a certain point ofdetail, particularly on non-material social and environmental issues, additional disclosure correlates with declining investor confidence, suggesting information overload orskepticism. This research contributes a more granular, contingent theory of CSR valuerelevance, challenging the prevailing ’more is better’ disclosure paradigm and offeringmanagers a strategic framework for prioritizing material CSR communication.